Analisis Kemampuan Literasi Sains Siswa Pondok Pesantren dalam Memecahkan Masalah Kesehatan Tubuh: Studi Kasus di Pondok Pesantren Mamba’us Sholihin 8 - Hasan, Efvysien Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2024)
This research aims to identify scientific literacy abilities in junior high school students living in Islamic boarding schools. It is hoped that the data obtained from this research will provide the latest information regarding students' scientific literacy abilities, especially those who live in Islamic boarding schools. The research uses a mixed method with a sequential explanatory design, which combines quantitative and qualitative methods sequentially. Quantitative data was collected through a scientific literacy test adapted from AKMI, while qualitative data was obtained through direct interviews with students and field observations. The research results show that the scientific literacy abilities of class IX students at Mamba'us Sholihin Middle School for the 2024/2025 academic year who live in Islamic boarding schools are in the medium category, with a percentage of 64%. Students still face difficulties in analyzing data, compiling syntheses, evaluating evidence, considering various opinions, compiling justified arguments, and designing steps to solve problems. Several factors that influence students' scientific literacy abilities include a lack of habit of working on scientific literacy questions, low interest in reading, as well as the influence of the environment, and a curriculum that does not support it optimally.